Is Climate Change making membership of CCAFS more important for farmers in Nepal? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Benup Aryal from PCPD, Nepal. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya